Substitution of Gly-548 to Ala in the Substrate Binding Pocket of Prothrombin Perijá Leads to the Loss of Thrombin Proteolytic Activity - Sekine, Osamu; Sugo, Teruko; Ebisawa, Kazuyoshi; Umeyama, Hideaki; Iwahana, Hiroyuki; Ruiz-Sáez, Arlette; de Bosch, Norma; Matsuda, Michio (Thrombosis and Haemostasis, 2002)
Prothrombin Perijá is a dysprothrombin derived from a homozygous patient that manifests low thrombin activity upon activation in a onestage assay. Purified prothrombin Perijá showed normal appearance on SDS-PAGE, and was cleaved normally to form α-thrombin by the prothrombinase complex. The activated form, thrombin Perijá, however, did not show any proteolytic activity towards native substrates, fibrinogen, protein C or various synthetic substrates for α-thrombin, but it was able to bind to antithrombin III, although the binding capacity was markedly reduced even in the presence of heparin. Thrombin Perijá showed full reactivity toward a small inhibitor, DFP, indicating that the molecular defect is in the substrate binding site in the thrombin molecule but not in the active site itself. By DNA sequence analysis of the patient prothrombin gene, we identified a G to C mutation at nucleotide 20016 in exon 14, which predicts a Gly-548 to Ala substitution in the prothrombin Perijá molecule. The structural modeling of thrombin Perijá suggests that Ala-548 is located close to the limb of the cavity wall of the substrate binding pocket, and that the methyl group blocks protrusion of the guanidino group of Arg into the cavity. This steric hindrance may well inhibit the access of Arg-containing substrates to the catalytic Ser-525 leading to the loss of proteolytic activity.
Keywords: Prothrombin; dysprothrombin; proteolytic activity; substrate binding pocket; steric hindrance